(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Analysis of the results of breech presentation for pregnant women with breech delivery from 22 weeks or more weeks gestation at Thai Nguyen Central Hospital from 2019 to 2023. Subjects and research methods: 150 medical records of expectant mothers diagnosed with breech presentation at gestational age of 22 weeks or more who gave birth at Thai Nguyen Central Hospital between January 1, 2029, and December 31, 2023, were included in this cross-sectional descriptive study technique. Results: Of all pregnancies, 68.7% ended in a full-term birth, whereas 31.3% resulted in a premature birth. The rate of cesarean section for breech babies was 77.3%. Most cases of breech babies had signs of labor, accounting for 95.3%. The rate of cesarean section due to simple breech babies was 31.9%, 68.1% had a combined cause. Cesarean section rates ranged from 68.2% in the 1600–2500 gram weight group to 90.5% in the 2600–3000 gram weight group and 100% in the group beyond 3000 gram. 98.7% of the infants were delivered without any issues. Conclusion: Most pregnant women with breech presentation terminate their pregnancy at term and by cesarean section. The rate of neonatal complications is low.